2021
DOI: 10.1021/acsmedchemlett.1c00140
|View full text |Cite
|
Sign up to set email alerts
|

Potent SARS-CoV-2 mRNA Cap Methyltransferase Inhibitors by Bioisosteric Replacement of Methionine in SAM Cosubstrate

Abstract: Viral mRNA cap methyltransferases (MTases) are emerging targets for the development of broad-spectrum antiviral agents. In this work, we designed potential SARS-CoV-2 MTase Nsp14 and Nsp16 inhibitors by using bioisosteric substitution of the sulfonium and amino acid substructures of the cosubstrate S-adenosylmethionine (SAM), which serves as the methyl donor in the enzymatic reaction. The synthetically accessible target structures were prioritized using molecular docking. Testing of the inhibitory activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…To our knowledge, only nonselective nanomolar inhibitors of nsp16 have been reported to‐date. 33 Although the MTase active site of nsp14 and nsp16, the two SARS‐CoV‐2 MTases, are quite different (Figure S1 ), our cross‐screening of inhibitors of nsp14 MTase activity against nsp10–nsp16 resulted in identifying SS148 and WZ16 as nsp16 MTase inhibitors. Our structural and biochemical assays elucidated a new mechanism of RNA‐dependent SAM‐competitive inhibition.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, only nonselective nanomolar inhibitors of nsp16 have been reported to‐date. 33 Although the MTase active site of nsp14 and nsp16, the two SARS‐CoV‐2 MTases, are quite different (Figure S1 ), our cross‐screening of inhibitors of nsp14 MTase activity against nsp10–nsp16 resulted in identifying SS148 and WZ16 as nsp16 MTase inhibitors. Our structural and biochemical assays elucidated a new mechanism of RNA‐dependent SAM‐competitive inhibition.…”
Section: Discussionmentioning
confidence: 92%
“…SARS‐CoV‐2 nsp10–nsp16 complex is an RNA MTase involved in RNA cap formation, enabling the virus to evade the immune system in humans. To our knowledge, only nonselective nanomolar inhibitors of nsp16 have been reported to‐date 33 . Although the MTase active site of nsp14 and nsp16, the two SARS‐CoV‐2 MTases, are quite different (Figure S1), our cross‐screening of inhibitors of nsp14 MTase activity against nsp10–nsp16 resulted in identifying SS148 and WZ16 as nsp16 MTase inhibitors.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, several studies have reported high-throughput screening of existing libraries of small molecules against nsp14 activity. However, very few compounds have been identified as potential inhibitors of SARS-CoV-2. In addition to the drug-repurposing approach, the method of de novo drug discovery with structure-guided design of nsp14 substrates yielded potent inhibitors with IC 50 values in the nanomolar to submicromolar range. , However, both articles did not report studies on the inhibitory activity of these nsp14 inhibitors in SARS-CoV-2-infected cells. Before the emergence of SARS-CoV-2, our group had pioneered the synthesis of selective inhibitors targeting the SARS-CoV nsp14 N 7-MTase using dinucleosides as mimetics of the S -adenosyl- l -methionine (SAM) that is the methyl donor in the N 7-methylation of the cap (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“… 17 19 There are potent S -adenosylhomocysteine (SAH)/SAM analogs that have been identified from a collection of other SAM-dependent MTase inhibitors 20 or rationally designed. 21 , 22 In addition, virtual screenings have been performed to identify potential Nsp14 MTase inhibitors. 23 However, most of these inhibitors are highly polar and no anti-SARS-CoV-2 activity has been reported.…”
mentioning
confidence: 99%
“…17 or rationally designed. 21,22 In addition, virtual screenings have been performed to identify potential Nsp14 MTase inhibitors. 23 However, most of these inhibitors are highly polar and no anti-SARS-CoV-2 activity has been reported.…”
mentioning
confidence: 99%